Stress and Anxiety among people with spiritist engagement: a cross-sectional analysis before and during COVID-19 (Research, Society and Development, 2023)
Prevalence of stress and anxiety in people with some Level of Spiritist Engagement (LSE) before and during the pandemic. A cross-sectional study with 848 people with LSE in Ceará/Brazil. Findings were significant on the severe stress and anxiety of young adults (15,0% and 15,9%, respectively), in marital crisis (17,1% and 15,9%), who were affected very/completely by social confinement (14,8% and 16,7%), who suffered violence (15,5% and 16,9%), who self-inflicted violence (29,4% and 35,3%), whose self-perception of the emotional health was bad/awful (35,7% and 33,9%), and that used 3 or more psychiatric drugs a day before (22,9% and 28,6%) and during the pandemic (31,6% for stress and anxiety). Severe stress and anxiety were more associated to low and very low LES before and during COVID-19. Spiritism reinforces itself as a religion of psychological quest and a higher LES seems to be connected to less severe anxiety and stress levels.